2022
DOI: 10.1021/acs.analchem.2c01370
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Boosted Fe, Co Dual Single-Atom Catalysts for Ultrasensitive Luminol-Dissolved O2 Electrochemiluminescence Detection of Prostate-Specific Antigen

Abstract: Improving the sensitivity of electrochemiluminescence (ECL) systems is highly desired for in vitro ECL diagnosis and bio-detections due to the often-low content of biomarkers in diseases. And dissolved O 2 (DO) as a co-reactant is considered superior to H 2 O 2 in the most commonly used luminol ECL systems due to better stability and low biotoxicity, but it still suffers from low ECL performance due to the low reactivity of DO. In this study, an efficient luminol-DO ECL system was developed through the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…According to the above experimental results, a brief summary of this CL reaction (Scheme ) is proposed as follows: (i) H 2 O 2 is adsorbed on the Zn-N sites, and Zn-N-C SACs efficiently catalyze the conversion of H 2 O 2 to O 2 · – ; (ii) the active O 2 · – oxidizes luminol to produce the excited 3-aminophthalate (3-AP*); (iii) the unstable 3-AP* returns to the ground state, accompanying light radiation. Furthermore, we used the Zn-N-C SACs to catalyze the electrogenerated chemiluminescence (ECL) of luminol according to the reported works about SACs for ECL. The Zn-N-C SACs could also catalyze the ECL of luminol-H 2 O 2 and luminol-dissolved O 2 , and the activity of the Zn-N-C SACs on the luminol-H 2 O 2 ECL system was higher than that on the luminol-dissolved O 2 ECL system (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above experimental results, a brief summary of this CL reaction (Scheme ) is proposed as follows: (i) H 2 O 2 is adsorbed on the Zn-N sites, and Zn-N-C SACs efficiently catalyze the conversion of H 2 O 2 to O 2 · – ; (ii) the active O 2 · – oxidizes luminol to produce the excited 3-aminophthalate (3-AP*); (iii) the unstable 3-AP* returns to the ground state, accompanying light radiation. Furthermore, we used the Zn-N-C SACs to catalyze the electrogenerated chemiluminescence (ECL) of luminol according to the reported works about SACs for ECL. The Zn-N-C SACs could also catalyze the ECL of luminol-H 2 O 2 and luminol-dissolved O 2 , and the activity of the Zn-N-C SACs on the luminol-H 2 O 2 ECL system was higher than that on the luminol-dissolved O 2 ECL system (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…In most recent years, single-atom catalysts (SACs) are emerging as an ongoing research hotspot in the catalysis field due to their unique advantages of maximum atom-utilization efficiency and high activity. , Benefiting from the fully exposed active sites, the fine electronic structures, unsaturated coordination environment, and strong metal-support interaction, SACs have been applied in many catalytic reactions (such as water splitting and nitrogen reduction). SACs have been demonstrated to display higher catalytic activity and selectivity, compared with their bulk and nanoparticle counterparts. , The outstanding catalytic activity and selectivity of SACs encourage researchers to explore SACs in the application of bioassay and biosensing for improving the sensitivity and/or selectivity. , Recently, SACs have been used to construct some colorimetric sensing, electrochemical sensing, and electrochemiluminescence sensing. , In the reported SAC-based sensing methods, the Fe-single atom is mainly used. , Although SACs have shown an outstanding role in the field of catalysis, the application of SACs for bioanalysis and sensing is still in their infancy stage at present. So, there remain significant opportunities and challenges that need to be addressed for SAC-based bioanalysis and sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the luminol/O 2 ECL system using Ni–N–C SAMs with Ni–N 4 active sites as co-reaction catalysts was successfully used for ascorbic acid detection. In another work, Jin et al reported the luminol/O 2 ECL system using Fe, Co–N–C dual SAMs and luminol-capped Ag nanoparticles as co-reaction catalysts, which can significantly activate dissolved O 2 to produce ROS . Although signal enhancement of the Fe, Co dual SAMs was low, the Ag nanoparticle-induced plasmon effect significantly boosted anodic ECL emission by a factor of 677.…”
Section: Electrochemiluminescence Sensors and Biosensorsmentioning
confidence: 99%
“…Surface plasmonic enhancements have been employed for amplifying the signal in biosensors [ 71 ]. This includes SPR [ 72 , 73 ], surface-enhanced Raman scattering (SERS) [ 74 ], surface-enhanced fluorescence (SEF), etc [ 75 ]. These surface plasmonic enhancement strategies have also been employed for SARS-CoV-2 detections in combination with smartphones.…”
Section: Smartphone-based Optical Analysismentioning
confidence: 99%